2020
DOI: 10.7150/ijms.42978
|View full text |Cite
|
Sign up to set email alerts
|

The extracts of Astragalus membranaceus overcome tumor immune tolerance by inhibition of tumor programmed cell death protein ligand-1 expression

Abstract: A polysaccharide isolated from the radix of Astragalus membranaceus, called PG2, used in traditional Chinese medicine, with potential hematopoiesis inducing and immunomodulation activities. PG2 extracted from A. membranaceus has been demonstrated as a novel alternative medicine for cancer patients. Recently, we demonstrated that PG2 enhanced chemotherapy through bystander effect and reduced the expression of indoleamine 2, 3-dioxygenase 1 in tumor cells. Many tumors have been proven to have a high expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…During in vitro and in vivo studies, apart from observing the effects on tumor cell proliferation, the related signaling pathways were explored, including the NF-kB and p38 MAPK signaling cascades mediated by TNFR1 in hepatocellular carcinoma cells (compound Kushen injection) (85) and the AKT pathway in gastric cancer and pancreatic cancer cells (Astragalus polysaccharide) (86,87). YIV-906, which is based on PHY906 (88), is a clinical observation drug that ensures >90% consistency in product quality (89). It is also the first Chinese medicinal project to be awarded a grant from the PO1 program of the National Cancer Center of the United States.…”
Section: Tcm Combined With Targeted Therapy or Immunotherapymentioning
confidence: 99%
“…During in vitro and in vivo studies, apart from observing the effects on tumor cell proliferation, the related signaling pathways were explored, including the NF-kB and p38 MAPK signaling cascades mediated by TNFR1 in hepatocellular carcinoma cells (compound Kushen injection) (85) and the AKT pathway in gastric cancer and pancreatic cancer cells (Astragalus polysaccharide) (86,87). YIV-906, which is based on PHY906 (88), is a clinical observation drug that ensures >90% consistency in product quality (89). It is also the first Chinese medicinal project to be awarded a grant from the PO1 program of the National Cancer Center of the United States.…”
Section: Tcm Combined With Targeted Therapy or Immunotherapymentioning
confidence: 99%
“…A study demonstrated that there was no significant difference in tumor inhibition compared with anti-PD-1 combined with ixabepilone or APS, indicating that APS can maintain an effective dose of anti-PD-1 antibody in vivo, and delay the progression of tumor or tumorigenesis by increasing the activity of T cells, which may improve the synergistic effect (Chang F.-L. et al, 2020). In addition, another research showed that APS enhances the chemotherapy by stimulating host immunity through reducing the PD-L1 expression of tumor surface (Chang H.-L. et al, 2020). It can reduce the expression of pro-inflammatory cytokines, promote the maturation of DCs and it also reduced the M2 macrophage population in patients with lung cancer (Huang et al, 2019).…”
Section: Astragalus Polysaccharidesmentioning
confidence: 96%
“…Polysaccharides (PG2) are a mixture of Astragalus polysaccharides (APS) with diverse biological actions, including immunomodulatory, anticancer, and neuroprotective properties [103]. Chang et al [104] reported that PG2 isolated from Astragalus can inhibit the tumour cell production of indoleamine 2,3-dioxygenase 1 and PD-L1, through the Akt/mTOR/p70S6K pathway, thereby downregulating cell surface PD-L1 expression and enhances cisplatin sensitivity.…”
Section: Irinotecan (Irt) Etoposide and Cisplatin (Cddp)mentioning
confidence: 99%